A preliminary study of visitors to ancient Merv (Turkmenistan). (1st January 2011) - Edwards, Jonathan; Vaughan, Roger
Merv was the first World Heritage Site in Turkmenistan to be designated, the site comprises early city-sites, religious or sacred buildings including the Mausoleum of Sultan Sanjar dating from the 12th century, and a shrine to honour the eminent 12th century Sufi scholar Hodja Yusup Hamadani which is a notable focus of pilgrimage. The aim of the paper is to determine a preliminary profile of visitors to a site which has historic and cultural significance for some and is a venue of shrine pilgrimage for others and review the respondent's assessment of the management of a visitor attraction where tribal traditions and Islamic beliefs and practices are a key consideration for visitors and site managers. The preliminary conclusions support are that following more than 100 years of Russian/Soviet colonisation the Turkmen Sufi inspired form of Islam integrated into a tribal society remains vibrant for an as yet undetermined percentage of the Turkmen nation.